(3GdEYLGR hGdEjLGRs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s ((3CMeO Hf eMeO Hf YHOGdZfj GHf GddHjH s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg hGdUdGI Ydi fHjg GdoeUWai hBdg aef GdcHGFQ Cf JSjQ eDdaGJj aj GdHdGO ejSQ GdCeKGd hdjS dj ajgG eDda HQSe GdTjN aj CMGSf GdfcJ eY LhGeY Gdcde, hHOGFY GddeY ef ehLRGJ GdZQQ s
(3BNQgG (B:s
(3hdg aj GdJgfFI HTghQ QeVGf, YqQac Gddg ef HQcGJg eG jQHj Ydi YOO GdUGFejf hGdbGFejf, aGFRG HGdeKhHI ef GdNGdb hGdTcQ ef GdeNdhbjf Je cJGH GdEYLGR hGdEjLGR s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B34 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs